Ofloxacin penetration into tuberculous pleural effusion. - Yew, W W (1991)
After 3 days of treatment with ofloxacin (300 mg given orally once daily), the drug levels in serum and pleural fluid 2 and 4 h after drug administration in patients with tuberculous pleural effusion were assessed by a rapid high-performance liquid chromatography assay. The levels in serum (mean +/- standard error of the mean [SEM]) were 4.70 +/- 0.14 and 4.63 +/- 0.09 mg/liter 2 and 4 h after administration, respectively, and the levels in pleural fluid (mean +/- SEM) were 3.82 +/- 0.09 and 4.21 +/- 0.08 mg/liter, respectively. The pleural fluid-to-serum ofloxacin ratio at 2 h was 0.82 +/- 0.02 (mean +/- SEM), and the ratio at 4 h was 0.92 +/- 0.02 (mean +/- SEM). This study demonstrated very good penetration of ofloxacin into pleural fluid in tuberculous pleuritis.